1987
DOI: 10.1007/bf00199299
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Bestatin immunotherapy in patients with transitional cell carcinoma of the bladder

Abstract: The first clinical results of an ongoing, prospective trial to determine the value of adjuvant Bestatin immunotherapy in the management of bladder cancer are presented. Patients with nonmetastatic transitional cell carcinoma of the bladder, scheduled for full dose local radiation therapy (64 Gy), were randomly allocated to adjuvant oral Bestatin treatment (30 mg daily for at least 1 year), starting at completion of irradiation, or no Bestatin. The longest follow-up period of the 151 evaluable patients is 6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The finding that targeting of a bcl-2 transgene rescued pre-B cells and immature B cells from dexamethasone-induced cell death indicates that Bcl-2 can regulate that response in early progenitors and early B cells. A differential susceptibility to cell death mediated by corticosteroid hormones has been previously demonstrated in thymocytes (Blomgren and Andersson, 1970;Cohen and Duke, 1984). Consistent with our findings in B cells, immature CD4+CD8+ thymocytes which express low levels of Bcl-2 are highly sensitive to dexamethasone-induced cell death.…”
Section: Pbs-controlsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that targeting of a bcl-2 transgene rescued pre-B cells and immature B cells from dexamethasone-induced cell death indicates that Bcl-2 can regulate that response in early progenitors and early B cells. A differential susceptibility to cell death mediated by corticosteroid hormones has been previously demonstrated in thymocytes (Blomgren and Andersson, 1970;Cohen and Duke, 1984). Consistent with our findings in B cells, immature CD4+CD8+ thymocytes which express low levels of Bcl-2 are highly sensitive to dexamethasone-induced cell death.…”
Section: Pbs-controlsupporting
confidence: 92%
“…Consistent with our findings in B cells, immature CD4+CD8+ thymocytes which express low levels of Bcl-2 are highly sensitive to dexamethasone-induced cell death. In contrast, mature single positive thymocytes which display high levels of Bcl-2 are more resistant (Blomgren and Andersson, 1970;Cohen and Duke, 1984). Previous experiments have shown that apoptosis induced by corticosteroid hormones in susceptible lymphoid cells can be inhibited by the overexpression of Bcl-2 from transfected gene constructs or transgenes (Sentman et al, 1991;Strasser et al, 1991b;Alnemri et al, 1992;Miyashita and Reed, 1992).…”
Section: Pbs-controlmentioning
confidence: 99%
“…We, as well as others, have undertaken a variety of immunomodulatory and immunotherapeutic studies with bestatin including therapeutic studies for metastases, solid tumors and autochthonous tumors [1, 3-5, 10, 13, 27, 31, 32, 33, 34]. In addition bestatin has shown therapeutic activity for acute nonlymphocytic leukemia as determined by a significant prolongation of survival [16,25] and for transitional cell carcinoma of the bladder on the basis of disease-free survival but not prolongation of survival [7]. However, additional studies on the optimal dose are needed for clarification of the therapeutic profile of bestatin in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…After screening, five RCTs (n=1372) met the criteria and were finally included in the study. 10,[13][14][15][16] Basic characteristics of included studies were showed in Table I. Bias risk assessment results were showed in Figure1, showing the type of bias and the total extent of the five studies included.…”
Section: Resultsmentioning
confidence: 99%